2020
DOI: 10.1101/2020.05.22.106195
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proper names from story recall are associated with beta-amyloid in cognitively unimpaired adults at risk for Alzheimer's disease

Abstract: Proper names from story recall are associated with beta-amyloid in cognitively unimpaired adults at risk for Alzheimer's disease ABSTRACT Due to advances in the early detection of Alzheimer's disease (AD) biomarkers including betaamyloid (Ab), neuropsychological measures that are sensitive to concurrent, subtle changes in cognition are critically needed. Story recall tasks have shown sensitivity to early memory declines in persons with Mild Cognitive Impairment and early stage dementia, as well as in persons w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Taken together, our findings show that impaired PN retrieval is associated with increased tau deposition in healthy older adults and shares features with episodic memory processes. As previous studies have acknowledged, PN retrieval measures may be able to identify subtle cognitive changes associated with early pathological processes 26 . In both a voxelwise and penalized regression setting, we have shown that in addition to the effect of entorhinal tau pathology there is a novel effect of fusiform tau and thickness.…”
Section: Discussionmentioning
confidence: 53%
“…Taken together, our findings show that impaired PN retrieval is associated with increased tau deposition in healthy older adults and shares features with episodic memory processes. As previous studies have acknowledged, PN retrieval measures may be able to identify subtle cognitive changes associated with early pathological processes 26 . In both a voxelwise and penalized regression setting, we have shown that in addition to the effect of entorhinal tau pathology there is a novel effect of fusiform tau and thickness.…”
Section: Discussionmentioning
confidence: 53%
“…Another potential limitation is the partial overlap between lexical features of the Story Recall items (e.g., nouns, verbs) and serial position. For instance, we know that recall of proper names is more predictive of subsequent amyloid burden than recall of common names (Mueller et al., 2020) and that proper names tend to appear more frequently at the start of the story (primacy region). Therefore, more research should be conducted to disentangle this potential conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Cognition and neuroprotection effects of CK Amyloid-β (Aβ) peptide is a biomarker of Alzheimer's disease (AD) (148). It has been shown that CK promotes the clearance of Aβ by enhancing autophagy in primary astrocytes and improves memory in scopolamine hydrobromide-injured mice by inhibiting Aβ accumulation and activating the Nrf2/Keap1 signaling pathway (123).…”
Section: Effects Of Ck On the Cnsmentioning
confidence: 99%